2022
DOI: 10.1002/suco.202200019
|View full text |Cite
|
Sign up to set email alerts
|

Impact resistance and mechanical properties of fiber‐reinforced concrete using string and fibrillated polypropylene fibers in a hybrid form

Abstract: In this study, the macro‐synthetic polypropylene fibers Forta and Barchip are used. The fibers are added at 0.5%, 1%, 1.5%, and 2% by weight of cement. Additionally, various fiber combinations with varying percentages are employed to create the concrete. Cubic specimens, bending beams, and impact specimens are all prepared on a percentage basis of fiber. The findings indicated that utilizing 1.5% fibrillated Forta fibers raised the compressive strength of the concrete by 18% and the flexural strength of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Existing research [47][48][49][50][51] shows that the splitting tensile damage of SFRC was closely related to the concrete matrix strength, steel fiber content and type. Previous studies showed 52 that the steel fiber undertook the main tensile stress after the concrete matrix was destroyed.…”
Section: Prediction Methods Of Splitting Tensile Strengthmentioning
confidence: 99%
“…Existing research [47][48][49][50][51] shows that the splitting tensile damage of SFRC was closely related to the concrete matrix strength, steel fiber content and type. Previous studies showed 52 that the steel fiber undertook the main tensile stress after the concrete matrix was destroyed.…”
Section: Prediction Methods Of Splitting Tensile Strengthmentioning
confidence: 99%
“…Similarly, in another study, GP was incorporated at 28.4% and 45% as a partial replacement for the sand for a design of 210 kg•cm -2 where the resistance was increased by 19% and 25% compared to the standard design, demonstrating an effect positive in both early strength and quality of concrete, as well as strength after 90 and 180 days of hardening (Ghorbani et al, 2019;Najaf & Abbasi, 2022b). Respect for the environment and the profitability of residual GP make it an acceptable and sustainable alternative construction material, indicating an enormous potential for GP as a replacement for natural fine aggregate (Singh, Khan, Khandelwal, Chugh & Nagar, 2016;Najaf & Abbasi, 2022a).…”
Section: Introductionmentioning
confidence: 94%
“…The use of recycled materials in the production of concrete is an issue that has generated interest among many researchers for the purpose of improving the environment (Najaf & Abbasi, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Such products can be used in the construction of pavements and overlays or concrete structures. For example, natural, synthetic, and industrial fibers such as steel fibers, 1–5 jute and kenaf fiber, 6–8 rice fiber, 9 glass fiber, 10–12 basalt fiber, 13 wool of animals, 14,15 and Forta aramid fibers 16–20 have been employed in previous works in the mix design of concrete materials. Review of literature also reveals that other industrial waste materials such as recycled stone and metal aggregates, rubber powders and granules, shredded PET, furnace slag aggregates, and powders are possible candidate materials to be utilized in the mix design of asphalt or concrete materials 21–29 …”
Section: Introductionmentioning
confidence: 99%